2022
DOI: 10.1111/inm.12977
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and challenges faced by community mental health workers when providing care to people with mental health conditions: A qualitative descriptive study

Abstract: The global prevalence of mental health conditions and the associated wide treatment gaps have led to increased demand for quality mental healthcare services. In Singapore, despite a shift towards a joint provision of mental healthcare in hospitals and the community, experiences of mental healthcare teams in such hospital‐community partnerships have remained unclear. Through a qualitative descriptive approach, this study explored community mental health workers’ experiences and perceptions of working with partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…This feeling of powerlessness is associated with burnout and negative job outcomes, which can drive more turnover [48]. These aspects eventually lead to early termination or delay of CMHS [49]. A study by Karkkola et al found that role clarity through higher autonomy and higher competence can impact subjective dynamics at work [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feeling of powerlessness is associated with burnout and negative job outcomes, which can drive more turnover [48]. These aspects eventually lead to early termination or delay of CMHS [49]. A study by Karkkola et al found that role clarity through higher autonomy and higher competence can impact subjective dynamics at work [50].…”
Section: Discussionmentioning
confidence: 99%
“…The CMHWs often find it difficult to obtain complete patient information and need to spend their time piecing it together. This is also the difficulty faced by CMHS in Singapore [49]. The lack of effective communication and cooperation makes the patient's information cannot be shared in time and become fragmented.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive decentralization of mental healthcare over recent decades might have partly been responsible for a fragmented medical system. This system not only relies on coordination between healthcare organizations, but also obliges individuals to establish and maintain contact with a multiplicity of such organizations ( 7 , 9 ). The fragmentation is further confounded by existing challenges in the treatment for people with psychiatric-somatic comorbidities ( 10 ) and by difficulties faced by people with SMIs in establishing a point of contact with medical professionals ( 11 ).…”
Section: Introductionmentioning
confidence: 99%